2004
DOI: 10.1111/j.1462-8902.2004.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Signalling pathways involved in retinal endothelial cell proliferation induced by advanced glycation end products: inhibitory effect of gliclazide

Abstract: Our results demonstrate the involvement of PKC, MAPK and NF-kappaB in AGE-induced BREC proliferation and VEGF expression. Gliclazide inhibits BREC proliferation by interfering with these intracellular signal transduction pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…It has also recently been reported that both gliclazide and antioxidants, such as vitamin E or N-acetyl-L-cysteine, inhibit the activation of intracellular signal transduction pathways (i.e. protein kinase C, mitogen-activated protein kinase or nuclear factor-κB) by advanced glycation endproducts (AGE) in cultured retinal endothelial cells, thereby prevent AGE-induced cell proliferation [42]. Therefore, it is rational to combine any antioxidant to gliclazide treatment in order to potentiate its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been reported that both gliclazide and antioxidants, such as vitamin E or N-acetyl-L-cysteine, inhibit the activation of intracellular signal transduction pathways (i.e. protein kinase C, mitogen-activated protein kinase or nuclear factor-κB) by advanced glycation endproducts (AGE) in cultured retinal endothelial cells, thereby prevent AGE-induced cell proliferation [42]. Therefore, it is rational to combine any antioxidant to gliclazide treatment in order to potentiate its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is expressed on the surface of a variety of cell types, including endothelial cell, smooth muscle cells, mononuclear phagocytes, neurons, cardiac myocytes, and hepatocytes [31]. AGE binding to RAGE results in activation of several intracellular signaling pathways [32][33][34]. This promotes an increase in oxidative stress and the generation of proinflammatory and prosclerotic cytokines, leading to the disturbances in cellular function that may result in diabetic complications [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results from the phosphorylation assays, treatment with SNAP, SNP, and 8-pCPT-cGMP inhibited AGE-enhanced STAT5 protein-DNA binding activities. On the other hand, recent studies have indicated that activation of the MAPK pathway is associated with AGE-increased cell proliferation (36,37). Therefore, we also examined whether NO-PKG regulates p42/p44 MAPK activity in NRK-49F cells treated with AGE.…”
Section: No Donors and Pkg Activator Block Age-induced Proliferation mentioning
confidence: 99%